Efficacy and safety of rituximab in the treatment of connective tissue disease-related interstitial lung disease - Caterina Vacchi; Andreina Manfredi; Giulia Cassone; Gian Luca Erre; Carlo Salvarani; Marco Sebastiani (BioExcel Publishing Ltd, 2021)
Interstitial lung disease (ILD) represents a severe pulmonary complication of connective tissue diseases, rheumatoid arthritis (RA), and antineutrophil cytoplasmic antibodyassociated vasculitis. Treatment of ILD, mainly based on immunosuppression, remains challenging. Rituximab (RTX), a monoclonal antibody binding to CD20, is considered a valuable therapeutic choice in cases of refractory ILD. Here, we review the available efficacy and safety data on the use of RTX in the treatment of rheumatic disease-related ILD. Despite controversial efficacy data, RTX seems to be able to stabilize or improve ILD related to RA and antisynthetase syndrome and in established and severe ILD complicating systemic sclerosis. Fewer data are available regarding ILD related to Sjögren syndrome, systemic lupus erythematosus, and antineutrophil cytoplasmic antibody-associated vasculitis. To date, few prospective studies are available and randomized trials are still ongoing with the purpose of exploring the role of RTX in this condition, including the supposed relationship between efficacy and ILD radiologic patterns and safety data, up to now derived mainly from RA studies. Despite an overall acceptable safety profile, concerns remain regarding an increased infectious disease risk in patients with ILD as well as possible lung toxicity and the increased rate of immune-mediated reactions in patients with connective tissue diseases. In conclusion, RTX is a relevant therapeutic option for rheumatic disease-related ILD despite the existing uncertainties; ongoing trials are expected to clarify its use.